Produksi Enzim Lakase Oleh jamur Trichoderma Asperellum Lbkurcci Dalam Bioreactor Tray Menggunakan Variasi Ukuran Substrat Jerami Padi Dan Induser CuSO4 Pada Fermentasi Kultur Padat - Gustina Gustina; Sri Helianty; Andi Dahliaty (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
Laccase is one of the ligninolityc enzymes that capable to degrade lignin. This ability can be used for the pretreatment of lignocellulosic materials in the bioethanol production and lignin degradation in pulp. There are diverse sources of laccase producing like fungi, plants and bacteria. In this research, the production of lacase enzyme using Trichoderma asperellum LBKURCC1 with bioreactor tray using solid state fermentation (SSF) method with rice straw substrate. The purpose of this study was to determine the effect of rice straw size and the addition of CuSO4 concentration to the highest production of lacase enzyme by Trichoderma asperellum LBKURCC1. Fermentation is carried out with variation of time 5, 6, 7, 8, 9 and 10 days with fermentation temperature ± 30ºC, substrate size ± 0.5 cm, 1.5 cm, and 3.0 cm with substrate thickness at tray ie 3 cm acetate buffer solution pH 5,5 and addition of CuSO4 0.5 g/l. Variations for the addition of CuSO4 concentration 0 g/l, 0.50 g/l and 1 g/l with substrate thickness on tray were 3 cm, size of rice straw 0.5 cm and acetate buffer solution pH 5.5. Small size can provide the highest value and the added concentration of CuSO4 given can increase the activity of the resulting lacase enzyme. However, too high CuSO4 concentrations result in decreased lacase enzyme activity. The results showed that the highest lacase enzyme activity was obtained on the size of rice straw ie 0.5 cm and 7 days of fermentation time with an average of 19.27 U/L and the highest lacase enzyme activity was obtained on CuSO4 0.50 g/l and fermentation time 7 day with an average of 19.27 U/L.Keywords: Inducer, Laccase, Rice straw, Solid state fermentation, Trichoderma asperellum.